EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA AL-ISLAM KRIAN SIDOARJO - Masfufah, Masfufah; Salsabilah, Nadifa; Zalsanudin, Virgie Ramadhani (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
The Problem Based Learning (PBL) learning model is an approach that focuses on problem-solving as a way to enhance student learning outcomes. This research aims to review the effectiveness of the PBL model in improving student learning outcomes, as well as critical thinking skills and problem-solving abilities. Based on the existing literature review, PBL has been proven to enhance student learning outcomes by making them more active in their learning, as they are directly involved in the problem-solving process relevant to real life. Additionally, PBL also develops collaboration and communication skills among students. However, the success of PBL implementation is influenced by various factors, such as teacher support, adequate school facilities, and parental support. Overall, PBL can improve student learning outcomes, both in academic aspects and life skills.Further research is needed to examine the application of PBL at various educational levels and subjects.